1991
DOI: 10.1172/jci115146
|View full text |Cite
|
Sign up to set email alerts
|

Brain natriuretic peptide as a novel cardiac hormone in humans. Evidence for an exquisite dual natriuretic peptide system, atrial natriuretic peptide and brain natriuretic peptide.

Abstract: IntroductionUsing a specific radioimmunoassay for human brain natriuretic peptide (hBNP) with a monoclonal antibody, we have investigated its synthesis, secretion, and clearance in comparison with those of atrial natriuretic peptide (ANP) in normal subjects and patients with congestive heart failure (CHF Since the discovery of atrial natriuretic peptide (ANP)' in the heart (1-5) and subsequently in the brain (5-10), ANP has been implicated in body fluid homeostasis and blood pressure control as a hormone and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

28
717
6
16

Year Published

1993
1993
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,263 publications
(773 citation statements)
references
References 51 publications
28
717
6
16
Order By: Relevance
“…ANP and BNP are secreted predominantly by the cardiac atrium and ventricle, respectively, in response to volume expansion and ventricular wall stress [9,11]. Increased cardiac secretion of BNP, as well as ANP, has been demonstrated in patients with cardiovascular diseases such as congestive heart failure, hypertension and renal failure, serving as one of the compensatory mechanisms against disease progression [11,12]. ANP and BNP share the same receptor, a particulate guanylyl cyclase (GC)-coupled receptor, or GC-A, and exert almost identical actions [13].…”
mentioning
confidence: 99%
“…ANP and BNP are secreted predominantly by the cardiac atrium and ventricle, respectively, in response to volume expansion and ventricular wall stress [9,11]. Increased cardiac secretion of BNP, as well as ANP, has been demonstrated in patients with cardiovascular diseases such as congestive heart failure, hypertension and renal failure, serving as one of the compensatory mechanisms against disease progression [11,12]. ANP and BNP share the same receptor, a particulate guanylyl cyclase (GC)-coupled receptor, or GC-A, and exert almost identical actions [13].…”
mentioning
confidence: 99%
“…BNP is a cardiac neurohormone specifically secreted from the ventricle in response to volume expansion and pressure overload (22)(23)(24)(25). BNP is a truly ventricular hormone, and responds to changes in LV filling pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Although the kinetics of atrial-derived BNP in heart failure are not fully known, some studies (23)(24)(25) propose that the atrium is the major source of secretion in the early stage of lowered cardiac function, and that BNP levels from the ventricle increase after the progression to heart failure. BNP and ANP are structurally similar, and BNP is probably also stored in secretion granules (16,33).…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier study (20) we had demonstrated that in conscious hypertensive transgenic rats with an extra renin gene (TG(m(Ren2)27)) a single administration of the NEP inhibitor ecadotril, the orally active prodrug of (S)-thiorphan, significantly increased plasma ANP levels (11). In rats with experimentally induced congestive heart failure (aortovenocaval fistula rats) acute treatment with ecadotril increased the plasma levels of endogenous ANP without having any effect in their sham-operated controls (21).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to ANP, cardiac hormone BNP is secreted predominantly from the ventricles of a hypertrophic h eart, and it is used as a marker for various stages of heart failure in humans (10). Mukoyama et al (11) have shown a higher percentage increase in plasma BNP than in plasma ANP in patients with CHF (11) and immediately after myocardial infarction (12). They also found a relationship between the plasma levels of BNP and both the degree of heart failure and that of left-ventricular dysfunction.…”
mentioning
confidence: 99%